CT Angiographic Appearance of In-Stent Restenosis of Intracranial Arteries Treated with the Wingspan Stent - Turk, A.S.; Rowley, H.A.; Niemann, D.B.; Fiorella, D.; Aagaard-Kienitz, B.; Pulfer, K.; Strother, C.M. (American Journal of Neuroradiology, 2007)
SUMMARY: Four patients underwent angioplasty and stenting of medically refractory symptomatic intracranial atherosclerosis with the new Wingspan stent system. In all 4 patients, CT angiography (CTA) showed an abnormality within the stented segment that was suggestive of nonocclusive in-stent thrombus. However, subsequent conventional angiography findings were typical for in-stent restenosis. The CTA imaging features of in-stent restenosis are important to recognize, and the misinterpretation of in-stent restenosis as in-stent thrombus may result in inappropriate management.